IBM z/OS V2R2 UNIX system services - Winnard, Keith; Hering, Paul-Robert (IBM Corporation, International Technical Support Organization, 2015)
This IBM® Redbooks® publication familiarizes you with the technical changes that were introduced into the UNIX System Services areas with IBM z/OS® V2R2. This book is one of a series of IBM Redbooks publications that take a modular approach to providing information about the updates that are included within z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful. We value your feedback.
Number on resource description page: SG24831000. - "z Systems.". - Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed January 21, 2016)
Keywords: z/OS; UNIX (Computer file); Database management; Bases de données; Gestion